Survey of Recent Developments - Armstrong, Shiro (Taylor and Francis, 2014)
As Indonesia heads to the polls in 2014, its economy is slowing. The end of the commodities boom and the global return to more normal monetary policy has exposed some weaknesses. Exchange-rate depreciation has absorbed some of the adjustment; but structural rigidities are still likely to limit the expansion of non-commodity sectors, and the increased fuel-subsidy bill for imported oil is putting pressure on the current account and the budget. The immediate focus is on demand-side consolidation to manage inflation and the current account deficit.